Serum Bone Resorption Markers after Parathyroidectomy for Renal Hyperparathyroidism: Correlation Analyses for the Cross-Linked N-telopeptide of Collagen I and Tartrate-Resistant Acid Phosphatase. (31st July 2012) - Hung, Kuo-Chin; Huang, Chung-Yu; Liu, Chuan-Chieh; Wu, Chih-Jen; Chen, Shao-Yuan; Chu, Pauling; Wu, Chia-Chao; Lo, Lan; Diang, Liang-Kuang; Lu, Kuo-Cheng
Abstract : Patients on long-term dialysis may develop secondary hyperparathyroidism (SHPT) with increased serum concentrations of bone resorption markers such as the cross-linked N-telopeptide of type I collagen (NTX) and type-5b tartrate-resistant acid phosphatase (TRAP). When SHPT proves refractory to treatment, parathyroidectomy (PTX) may be needed. Renal patients on maintenance HD who received PTX for refractory SHPT (n = 23 ) or who did not develop refractory SHPT (control subjects; n = 25 ) were followed prospectively for 4 weeks. Serum intact parathyroid hormone (iPTH), NTX, TRAP, and bone alkaline phosphatase (BAP) concentrations were measured serially and correlation analyses were performed. iPTH values decreased rapidly and dramatically. BAP values increased progressively with peak increases observed at 2 weeks after surgery. NTX and TRAP values decreased concurrently and progressively through 4 weeks following PTX. A significant correlation between TRAP and NTX values was observed before PTX but not at 4 weeks after PTX. Additionally, the fractional changes in serum TRAP were larger than those in serum NTX at all times examined after PTX. Serum iPTH, TRAP, and NTX values declined rapidly following PTX for SHPT. Serum TRAP values declined to greater degrees than serum NTX values throughout the 4-week period following PTX.